Frailty and long-term survival of patients with ovarian cancer: A systematic review and meta-analysis - Li, Kemin; Yin, Rutie; Li, Zhengyu (Frontiers in Oncology, 2022)
Background: Frailty has been related with poor prognosis of various diseases, including ovarian cancer. We performed a systematic review and meta-analysis to evaluate the association between frailty and long-term survival of patients with ovarian cancer. Methods: Relevant cohort studies were retrieved by search of PubMed, Embase, Cochrane’s Library, and Web of Science electronic databases. Two authors independently performed literature search, data collection, and statistical analyses. A random-effect model incorporating the possible influence of heterogeneity was used to pool the results. Results: Nine cohort studies including 2497 women with confirmed diagnosis of ovarian cancer contributed to the meta-analysis, and 536 (21.5%) of them were with high frailty. The median follow-up durations varied between 24 and 69 months. Compared to patients with low or non-frailty, OC patients with high frailty were associated with poor overall survival (risk ratio [RR]: 1.61, 95% confidence interval [CI]: 1.41 to 1.85, p < 0.001; I2 = 0%) and progression-free survival (RR: 1.51, 95% CI: 1.20 to 1.89, p < 0.001; I2 = 0%). Subgroup analyses according to study design, cancer stage, age of patients, scales for frailty evaluation, follow-up duration, and quality score of the included study showed consistent association between high frailty and poor overall survival in women with ovarian cancer (p for subgroup effects all < 0.05). After considering GRADE criteria for strength of the evidence, it was rated low for both the two outcomes. Conclusion: High frailty may be an independent risk factor of poor survival in women with ovarian cancer. Evaluating frailty may be important for predicting the prognosis and determining the optimal anticancer treatments in women with ovarian cancer.